Improving the Vertical Modeling of Tropospheric Delay. Issue 5 (8th March 2022) - Wang, Jungang; Balidakis, Kyriakos; Zus, Florian; Chang, Xiao; Ge, Maorong; Heinkelmann, Robert; Schuh, Harald
Abstract: Accurate tropospheric delays from Numerical Weather Models (NWM) are an important input to space geodetic techniques, especially for precise real‐time Global Navigation Satellite Systems, which are indispensable to earthquake and tsunami early warning systems as well as weather forecasting. The NWM‐based tropospheric delays are currently provided either site‐specific with a limited spatial coverage, or on two‐dimensional grids close to the Earth surface, which cannot be used for high altitudes. We introduce a new method of representing NWM‐derived tropospheric zenith hydrostatic and wet delays. A large volume of NWM‐derived data is parameterized with surface values and additional two or three coefficients for their vertical scaling to heights up to 14 km. A precision of 1–2 mm is achieved for reconstructing delays to the NWM‐determined delays at any altitudes. The method can efficiently deliver NWM‐derived tropospheric delays to a broader community of space geodetic techniques. Plain Language Summary: Precise positioning with microwave‐based space geodetic techniques, such as Global Navigation Satellite Systems (GNSS), requires accurate modeling of the atmospheric refraction. Numerical Weather Models (NWM) can provide tropospheric delays with an accuracy of 1–2 cm in zenith direction and are therefore useful for improving the data analysis. However, due to the large data volume to handle, NWM‐based products are typically provided only for selected sites, or on a global grid referring to a specific height. We provide an efficient method to represent the vertical profile of tropospheric delay from the Earth surface up to 14 km altitude with a precision of 1–2 mm. The method is used to preserve the precision of NWM‐derived tropospheric delays at the altitudes using three to four coefficients per geographic location (longitude, latitude) at the ground. This paves the way of applying the NWM‐based accurate tropospheric delays in space geodetic data analysis, especially for global augmentations of real‐time GNSS, which play a critical role in the rapid characterization and early warning of geohazards such as earthquake and tsunami, as well as kinematic platforms of high altitudes. Key Points: New method for precise modeling of the zenith hydrostatic and wet delays from the Earth surface up to an altitude of 14 km Tropospheric delay vertical modeling precision of better than 3 mm is achieved on a global scale The method provides numerical weather model‐derived precise tropospheric augmentation correction for real‐time space geodetic techniques